Taking Selfies in Auschwitz. What Sense for Dark Tourism? - Violi, Patrizia (E|C, 2022)
In my contribution I will analyse that contemporary form of tourism commonly called "dark tourism", concemed with places of mass murders and genocides. In particular, I will discuss motivations and behaviours of visitors, with reference to installations and documentaries - in the respective works of israeli-german writer Shahak Shapira and ukraine director Sergei Loznitsa - which problematize the touristic visits of such places. Doing so, I will attempt to deepen into the problem of legitimacy and semiotic effectiveness of these forms of memorialization. The issue is related to the present and future meanings of tourism itself, but it is also at the very core of what is socially meant to be the collective past.